An assessment of anticompetitive conduct in the supermarkets sector in Costa Rica - Miranda Montes, Donald (2016)
The studies were based on the assumption, common to all advocates of competition policy, that a workably competitive marketplace is achievable where private impediments to competition are removed and that government intervention to that end may both be necessary and possible. The book thus also discusses the types of intervention and representation that the competition authorities could make in each case, including both direct interventions aimed at correcting market failings and other measures intended to empower the authorities within their respective national governance systems.